Catalytic and antibacterial properties of 3‐dentate carboxamide Pd/Pt complexes obtained via a benign route. (3rd February 2020) - Kiani, Mahsa; Bagherzadeh, Mojtaba; Meghdadi, Soraya; Fadaei‐Tirani, Farzaneh; Schenk‐Joß, Kurt; Rabiee, Navid
Abstract : The complexes Pd II (qcq)(OAc) and Pt II (qcq)Cl have been synthesized using environmentally benign synthesized ligands and characterized by elemental analyses: Fourier transform infrared spectroscopy, UV–visible spectroscopy, 1 H NMR spectroscopy, and X‐ray diffraction. The catalytic activity of the complex was assessed, in different media, for the Mizoroki–Heck coupling reaction for typical aryl halides and terminal olefins under aerobic conditions. Since the base and the solvent were found to influence the efficiency of the reaction, reaction conditions, temperature, time, and the amount of K3 PO4 and a mixture of H2 O/PEG, were optimized. We found, for the Mizoroki–Heck reaction coupling less reactive aryl chloride derivatives with olefins, promising activity for palladium catalysts. The electrochemical behavior of Hqcq and the Pd(II) complex was investigated by cyclic voltammetry and irreversible Pd II/I reductions were observed. Hqcq and the Pd(II) and Pt(II) complexes were also screened for their in vitro antibacterial activity. They showed promising antibacterial activity comparable to that of the antibiotic penicillin. Abstract : Two Pd(II) and Pt(II) carboxamide complexes were synthesized. The catalytic activity of the Pd(II) complex was assessed in different media. We found, for the Mizoroki‐Heck reaction coupling less reactive aryl chloridederivatives with olefins, promising activity for palladium catalysts.